Impact Of Servicescape Failures And Associated Recovery Strategies On Customer Behavior In The Food Service Industry - Chua, Bee Lia (2009)

(untitled)
Servicescape has become an increasingly important element in the delivery of customers’ expectation and delight in services industry. However, servicescape failure can result in customer dissatisfaction. The subsequent interaction with a service employee has a great deal of influence on customer ultimate satisfaction. Despite the acknowledged importance of servicescape and effective recovery strategy, there is a dearth of investigation on servicescape failure and the associated recovery strategy, and the influence of these on customers’ subsequent behaviors, particularly in the food service industry. This study attempted to fill the research gaps by examining the effect of customers’ responses to servicescape failure and satisfaction of recovery strategy on repatronage behavior and word-of-mouth communication. The Critical Incident Technique (CIT) was used to examine customers’ behaviors associated with servicescape failures and recovery strategies in the food service industry. Food service industry was chosen because it involves a high level of service involvement among customers and is consumed and evaluated in a single episode by the customers. In-depth personal interview was applied because it provides a rare glimpse into how customers respond to servicescape failures and evaluate recovery strategies effectiveness. The transcription was content analyzed through an inductive sorting process to classify data categories that summarize and describe the research phenomenon. The developed classification system was measured by inter-judge reliability and content validity. Using the CIT, data on 226 servicescape failures and 287 recovery actions were collected from 174 informants by the personal interview. The analysis revealed that cleanliness issues (76.1%) were the most reported problem in the food service industry, followed by design issues (11.1%), social interaction issues (7.1%), and functionality issues (5.7%). Customers exhibited negative reactions to those failures with displaying of emotional (angry, annoyed, disgusted, disappointed, unhappy, shocked, embarrassed, and frustrated) and physiological (sweat, eyes pain, body hurts, and itchy) responses. The recovery strategies identified through the sorting process resulting in five major categories which were empathetic, corrective, compensatory, authority intervention, and no recovery. The implemented recoveries were perceived positively and negatively by the customers. Combination of prompt action-oriented responses and sincere empathetic responses was perceived as far more effective and was likely to meet customers satisfaction, regardless of servicescape failure type. A simple apology or explanation did nothing to resolve the customer’s need for immediate action; meanwhile, an action without empathetic response did not ensure customer satisfaction. Customers were most likely not to repatronize the same eatery if they were dissatisfied with the servicescape as well as the way the food service employee handled the complaint. Dissatisfied customers did engage in word-of-mouth communication than satisfied customers. It is apparent that servicescape failures when combined with inappropriate recovery efforts can significantly affect customers’ behavioral responses. This study has implications for food service managers and/or practitioners who are seeking to improve the tangibles in their eateries. It is recommended that food service managers have to closely monitor the servicescapes and implement appropriate recovery strategies which may greatly affect customer satisfaction and future behaviors. Food service managers not only need to address issues that could minimize the occurrence of servicescape failures but also need to discuss specific and desired recovery efforts. Staff training is a necessary process in developing efficient and effective service delivery systems. Keywords: servicescape failure; recovery strategy; repatronage behavior; word-of-mouth communication; food service industry; critical incident technique